2016
DOI: 10.1039/c6tb01388k
|View full text |Cite
|
Sign up to set email alerts
|

Photo-antimicrobial polymeric films releasing nitric oxide with fluorescence reporting under visible light

Abstract: A novel photoresponsive molecular hybrid has been embedded in poly(lactic-co-glycolic acid) (PLGA) to give an antibacterial polymeric film generating nitric oxide (NO) under visible light, with concomitant fluorescence reporting of NO release. The molecular hybrid integrates a nitroaniline NO photodonor and a coumarin latent fluorophore in the same molecular skeleton and results in quite homogeneous distribution in the polymer matrix where it preserves well the photobehavior exhibited in solution. The doped PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…As a prominent gasotransmitter, NO has been demonstrated to influence abundant physiological processes including cell apoptosis, angiogenesis, immune responses, neurotransmission, etc . Therefore, NO has been extensively explored in versatile biomedical applications such as cardiovascular homeostasis, bone metabolism and neurotransmission, respiratory diseases, antimicrobial therapy, wound healing, and antibacterial . Especially, NO can efficiently kill the cancer cells via the nitrosation of mitochondria and DNA, paving the new way for NO‐induced cancer therapy .…”
Section: Nitric Oxide (No)‐generating Ggnsmentioning
confidence: 99%
“…As a prominent gasotransmitter, NO has been demonstrated to influence abundant physiological processes including cell apoptosis, angiogenesis, immune responses, neurotransmission, etc . Therefore, NO has been extensively explored in versatile biomedical applications such as cardiovascular homeostasis, bone metabolism and neurotransmission, respiratory diseases, antimicrobial therapy, wound healing, and antibacterial . Especially, NO can efficiently kill the cancer cells via the nitrosation of mitochondria and DNA, paving the new way for NO‐induced cancer therapy .…”
Section: Nitric Oxide (No)‐generating Ggnsmentioning
confidence: 99%
“…Although several strategies describing the synthesis of biodegradable synthetic polymers either chemically modified with NO donors or prepared as polymeric nanoparticles for the encapsulation of NO-releasing small molecules have been reported, the majority of these materials are limited to polyesters such as poly(lactic-co-glycolic acid), [56] poly(sulfhydrylated polyester) [57] , poly(glycerol-co-glutaric acid), [58] and poly(citric-co-maleic acid-co-1,8-octanediol). [59] Reynolds and co-workers have worked to expand this area by developing S -nitrosothiol-modified poly(organophosphazenes) (POP) systems that can degrade hydrolytically into non-toxic phosphate and ammonia.…”
Section: Macromolecular Nitric Oxide Donorsmentioning
confidence: 99%
“…For example, of polyethylene glycol and poly(lactic-co-glycolic acid) modifications have been shown to reduce hydrophobicity and improve degradability of the scaffolds, respectively. [56, 65, 75−76, 82a] Recent work has begun to evaluate the use of naturally produced biopolymers as NO-release scaffolds, including dextran and chitosan with inherently favorable toxicity and biodegradability properties. [47, 86] For instance, Lu et al reported on NO-releasing chitosan oligosaccharides that proved non-toxic to mouse fibroblasts at their MBEC, indicating an advantage of these materials compared to other antibacterial agents.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Recent progresses in the field include visible light controlled NO donors, e.g. PPIX/AFX/Fluor-RSE [36][37][38] , FlEt [39] , BODIPY labled NONOates [33] , o-trifluoromethyl nitrobenzene [40,41] and NOBL-1 [42] (Figute 1).We recently proposed to develop NO donors with both a robust photo-trigger to render a spatiotemporal control of NO release, and a built-in calibration mechanism in form of a concomitant fluorescence turn-on to allow convenient monitoring of NO release. The first embodiment of such photo-triggered and photo-calibrated NO donors is Nnitrosated naphthalimides (NOD545) [43] , whose scope of applications is however limited by the fact that a UV light at 365 nm was in need to trigger NO release.…”
mentioning
confidence: 99%
“…Recent progresses in the field include visible light controlled NO donors, e.g. PPIX/AFX/Fluor-RSE [36][37][38] , FlEt [39] , BODIPY labled NONOates [33] , o-trifluoromethyl nitrobenzene [40,41] and NOBL-1 [42] (Figute 1).…”
mentioning
confidence: 99%